Freehand Minimally Invasive Pedicle Screw Fixation and Minimally Invasive Decompression for a Thoracic or Lumbar Vertebral Metastatic Tumor From Hepatocellular Carcinoma - Wenshuai Fan (Frontiers Media S.A., 2021)
Objective: To compare freehand minimally invasive pedicle screw fixation (freehand MIPS) combined with percutaneous vertebroplasty (PVP), minimally invasive decompression, and partial tumor resection with open surgery for treatment of thoracic or lumbar vertebral metastasis of hepatocellular carcinoma (HCC) with symptoms of neurologic compression, and evaluate its feasibility, efficacy, and safety.Methods: Forty-seven patients with 1-level HCC metastatic thoracolumbar tumor and neurologic symptoms were included between February 2015 and April 2017. Among them, 21 patients underwent freehand MIPS combined with PVP, minimally invasive decompression, and partial tumor resection (group 1), while 26 patients were treated with open surgery (group 2). Duration of operation, blood loss, times of fluoroscopy, incision length, and stay in hospital were compared between the two groups. Pre- and postoperative visual analog scale (VAS) pain score, Oswestry Disability Index (ODI), American Spinal Injury Association (ASIA) grade, ambulatory status, and urinary continence were also recorded. The Cobb angle and central and anterior vertebral body height were measured on lateral radiographs before surgery and during follow-ups.Results: Patients in group 1 showed significantly less blood loss (195.5 ± 169.1 ml vs. 873.1 ± 317.9 ml, P = 0.000), shorter incision length (3.4 ± 0.3 vs. 13.6 ± 1.8 cm, P = 0.000), shorter median stay in hospital (4–8/6 vs. 8–17/12 days, P = 0.000), more median times of fluoroscopy (5–11/6 vs. 4–7/5 times, P = 0.000), and longer duration of operation (204.8 ± 12.1 vs. 171.0 ± 12.0 min, P = 0.000) than group 2. Though VAS significantly decreased after surgery in both groups, VAS of group 1 was significantly lower than that of group 2 immediately after surgery and during follow-ups (P < 0.05). Similar results were found in ODI. No differences in the neurological improvement and spinal stability were observed between the two groups.Conclusion: Freehand MIPS combined with PVP, minimally invasive decompression, and partial tumor resection is a safe, effective, and minimally invasive method for treating thoracolumbar metastatic tumors of HCC, with less blood loss, better pain relief, and shorter length of midline incision and stay in hospital.